Ultra-low friction self-levitating nanomagnetic fluid bearing for highly efficient wind energy harvesting. (August 2022) - Pathak, Saurabh; Zhang, Ran; Gayen, Bishakhdatta; Kumar, Vinod; Zhang, Hui; Pant, R.P.; Wang, Xu
Abstract: Wind energy provides one of the most sustainable and cleanest forms of energy conversion to tackle the biggest global concern of CO2 emissions from the use of fossil fuels. It is also challenging to build an efficient energy harvester to minimize the losses at several levels during the electrical energy conversion. Herein, we have proposed a novel wind energy harvester that capitalizes on the self-levitation nanomagnetic fluid bearing. The magnetic fluid contains magnetic nanoparticles which sticks to the magnets forming bearing around the edges and providing magnets a passive levitation, which eventually results in an ultra-low frictional surface between the permanent magnet and bottom support surface. The motion of the magnets attached to the rotating fan-shaft assembly driven by the blades and input blowing wind relative to the fixed coils induces a current in the coil. The mechanism has been effectively utilized to develop a highly efficient prototype wind energy harvester, which runs at a very low wind speed of 2 m/s. The prototype wind energy harvester promises to generate 2.59Watt power with an efficiency of 26% at a gentle wind speed (4.5 m/s). Simulations are conducted to support the experimental results of the prototype and the simulation model is further extended to upscale the harvested power for more realistic applications. Our invention has a tremendous potential to produce highly efficient wind energy conversion at a large scale by solving the major problem in the current wind energy conversion systems.